2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5627619
|View full text |Cite
|
Sign up to set email alerts
|

Skull segmentation in 3D neonatal MRI using hybrid Hopfield Neural Network

Abstract: A fully automated method for segmentation of neonatal skull in Magnetic Resonance (MR) images for source localization of electrical/magnetic encephalography (EEG/MEG) signals is proposed. Finding the source of these signals shows the origin of an abnormality. We propose a hybrid algorithm in which a Bayesian classifying framework is combined with a Hopfield Neural Network (HNN) for neonatal skull segmentation. Due to the non-homogeneity of skull intensities in MR images, local statistical parameters are used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Nevertheless most algorithms have reported good results on par or better than previously published works. In particular, Daliri et al [29] have shown an improvement in SI values compared to Ghadimi et al [36]; Peporte et al [71] have also reported better performance of their approach compared to four publicly available brain extraction tools, namely, BrainSuite 6 , SPM8-Statistical Parametric Mapping 7 , FMRIB Software Library (FSL) 8 and MRIcroN 9 . Likewise, Mahapatra [58] has demonstrated better accuracy of their results in relation to the graph cut approach of Sadananthan et al [83] and other publicly available software like BET [97], BSE [89] and Hybrid Watershed Algorithm (HWA) [86] that is a part of FreeSurfer Software Suite 10 .…”
Section: Validation Of Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Nevertheless most algorithms have reported good results on par or better than previously published works. In particular, Daliri et al [29] have shown an improvement in SI values compared to Ghadimi et al [36]; Peporte et al [71] have also reported better performance of their approach compared to four publicly available brain extraction tools, namely, BrainSuite 6 , SPM8-Statistical Parametric Mapping 7 , FMRIB Software Library (FSL) 8 and MRIcroN 9 . Likewise, Mahapatra [58] has demonstrated better accuracy of their results in relation to the graph cut approach of Sadananthan et al [83] and other publicly available software like BET [97], BSE [89] and Hybrid Watershed Algorithm (HWA) [86] that is a part of FreeSurfer Software Suite 10 .…”
Section: Validation Of Resultsmentioning
confidence: 94%
“…This was followed by a level set based reconstruction to obtain closed surfaces. One other work that employed a probabilistic atlas for skull segmentation is that of Daliri et al [29]. This approach proposed an adaptive algorithm using Bayesian classifier to weight local features of the MR image against those of the atlas.…”
Section: Segmentation Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Image segmentation plays an important role in variety of applications such as robot vision, object recognition, geographical imaging and medical imaging [1][2][3][4][5][6]. In general, fuzzy segmentation methods, especially the FCM algorithm, have been widely used in image segmentation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%